PERTANGGUNGJAWABAN PIDANA TERHADAP ANGGOTA TENTARA NASIONAL INDONESIA YANG MELAKUKAN DESERSI (Studi Putusan Pengadilan Militer Nomor 198-K/PM I 02/AD/X/2017) - Nanang Tomi Sitorus; Madiasa Ablisar; Muhammad Hamdan; Marlina Marlina (Universitas Sumatera Utara, 2018)
Abstract Desertion is a crime that is specifically done by the military because of a legal fight and are contrary to the law, in particular the military criminal law. Enforcement of military discipline regulations of law discipline soldiers, where the regulations restrict all movement and behavior of soldiers. However, in practice, how strict the rules does not make the TNI soldiers dutifully, even likely to violate. This is still a lot of soldiers of the indonesian military who often unity on each felony desertion. The crime of desertion is common in military life, especially in the region of Kodam I Bukit Barisan, recorded in the year 2016 the number of perpetrators of crimes of desertion was litigated and 36 in the year 2017 totaled 6 things. The crime of desertion that often occur in the region of Kodam I Bukit Barisan are the crimes of desertion in time of peace, where the crime was committed when the country in peace and not in a State of war. The implications of this frequent desertions crime, poses a very significant influence especially against TNI soldiers on duty at the border in urban as well as remote areas, so that these influences can undermine mental and the personality of the TNI soldiers and damaging a military life joints and the image of the air force. The methods used in this research is the juridical normative legal research methods, i.e. a method by means of data collection based on the study of librarianship (library research) that is by way of examining data in the form of primary legal materials from secondary as scientific books, legislation, court decision I-02 Military terrain and data obtained by accessing the internet related to this research. The judicial process against the defendants on behalf of private first class Butar-Butar Suryadi Ahmad was held in a military Court I-02 Field. The process starts from the level of investigation by military police Subdenpom-I/1-4 Range, the submission of case by Danrem-022/PT as an officer of Subsmisson a cases, a military judge advocate (Requisitoir) as a public prosecutor and the judge's Verdict in the trial. The process of the trial is that the defendant is declared guilty of convincing has been conducting a legitimate absence without permission from superiors or desertion in time of peace as provided for in Article 87 paragraph (1) of the 2nd verse junto (2) Book The Act Of Military Criminal Law (KUHPM). Criminal liability against the defendant, by the Military Court judge I-02 Field in the form of criminal sanctions subject matter i.e. imprisonment for 5 (five) months and additional criminal was dismissed from military service. Keywords: Criminal Liability, The Indonesia National Army, Desertion.